Aspects prioritisation / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The Risk Priority Number (RPN) for each aspect description is determined by the following formula based on EMS ISO 14001. The impact ranking is important in determining the significant environmental impacts and in prioritising the mitigation measures. The rating description for aspects of prioritisation is shown in Table 4.2